2019
DOI: 10.3390/nu11061243
|View full text |Cite
|
Sign up to set email alerts
|

Bone Health, Body Composition, and Vitamin D Status of Black Preadolescent Children in South Africa

Abstract: Optimal bone health is important in children to reduce the risk of osteoporosis later in life. Both body composition and vitamin D play an important role in bone health. This study aimed to describe bone health, body composition, and vitamin D status, and the relationship between these among a group of conveniently sampled black preadolescent South African children (n = 84) using a cross-sectional study. Body composition, bone mineral density (BMD), and bone mineral content (BMC) were assessed using dual x-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
5
11
3
Order By: Relevance
“…Furthermore, the girls also had lower levels of physical activity as compared to boys, re ecting less outdoor activities and exposure to the sun. However, neither our study nor a similar study among preadolescent children in South Africa with low levels of serum vitamin D showed any association between bone parameters and levels of 25(OH)D (31).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the girls also had lower levels of physical activity as compared to boys, re ecting less outdoor activities and exposure to the sun. However, neither our study nor a similar study among preadolescent children in South Africa with low levels of serum vitamin D showed any association between bone parameters and levels of 25(OH)D (31).…”
Section: Discussioncontrasting
confidence: 99%
“…Two published studies from India and Iran amongst adolescents (mean age ranged from 13.2-15.4 years old) reported a positive association between lean mass and bone parameters as measured by DXA (27,28). The magnitude of the correlation between LM with BMC and BMD (0.8 and above) in the present study is similar to the studies reported in Caucasian children of a similar age group (29)(30)(31).…”
Section: Discussionsupporting
confidence: 88%
“…Two published studies from India and Iran amongst adolescents (mean age ranged from 13.2-15.4 years old) reported a positive association between lean mass and bone parameters as measured by DXA [31,32]. The effect of the association between LM with BMC and BMD (standardised β = 0.5to 0.8) were similar to the studies reported in Caucasian children of a similar age group [33][34][35]. Furthermore, our finding is aligned with the systematic review by Sioen et al [8]which reported that LM was a stronger determinant of bone parameters as measured by DXA than FM and BF %.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have reported a positive association between BMD and serum 25(OH)D levels in early and late pubertal children [ 37 , 38 , 39 ]. However, other studies, like ours, have not found any association between vitamin D status and BMD in pre-adolescent children [ 40 , 41 ]. Yang et al [ 42 ] examined the association of vitamin D status at different stages of growth with bone measures at 8, 16, and 25 years old, and they suggested that vitamin D status at the youngest age of 8 years old may not be as important as during adolescence in influencing BMD during young adulthood.…”
Section: Discussioncontrasting
confidence: 65%
“…Yang et al [ 42 ] examined the association of vitamin D status at different stages of growth with bone measures at 8, 16, and 25 years old, and they suggested that vitamin D status at the youngest age of 8 years old may not be as important as during adolescence in influencing BMD during young adulthood. The BMD and BMC of the children in this age-group could also be more easily determined by body weight and lean mass than by vitamin D status [ 41 , 43 ]. Hence, a prospective longitudinal study design would better verify the associations between 25(OH)D and associated changes in BMD in our population.…”
Section: Discussionmentioning
confidence: 99%